Validity of the PjBL-APCP Learning Model: Building a Teacherpreneur Mindset as an Action Plan to Solve Science Learning Problems for teacher candidate 21st Century - Anjarwati, Ani; Susantini, Endang; Rahayu, Yuni Sri (Education, Science, and Technology International Conference, 2025)
To prepare graduates who are ready to compete and adapt to the demands of the 21st century, effective educational strategies must be implemented. Among the essential competencies for this era is the ability to create innovative solutions for emerging problems an ability closely associated with entrepreneurial thinking. Teachers who demonstrate entrepreneurial traits are often referred to as teacherpreneurs. The “Project-Based Learning with Action Plan as Core Project” (PjBL-APCP) model was designed to cultivate this mindset among future educators. This study focuses on validating the PjBL-APCP model using a developmental research approach, specifically a validation study. The validation process assessed two key dimensions: (1) content validity, also known as relevance, and (2) construct validity, which refers to internal consistency. The validation was conducted with input from three experts in science education, utilizing structured validation sheets. Findings from the research and analysis indicate that the PjBL-APCP model demonstrates strong alignment and coherence, supported by very valid and reliable results (agreement rate ≥ 75%). The model is structured into seven sequential stages: (1) Identifying Potential, (2) Stimulating Instinct, (3) Concept Development, (4) Strategic Management, (5) Cultivating Sharing and Compassion, (6) Sustainability, and (7) Collaborative Engagement. Supporting tools used during the implementation process such as the Semester Learning Plan (RPS) and Student Activity Sheets (LAM 01 to LAM 04) were also verified as valid and reliable. Overall, the PjBL-APCP model shows promise in fostering teacherpreneurship by equipping prospective science teachers with actionable strategies to address 21st-century educational challenges.